Tara Miller: capstone - Miller, Tara, artist (Colorado State University. Libraries, 2015)
The artist's statement: Inspiration is everywhere and as a graphic designer my goal is to create work that accurately encapsulates what my clients envision and illustrates what inspires them. Each new client not only provides an opportunity to create, but also an opportunity to learn. Process plays an important role in my method of design. When a new assignment is introduced, my first step is to learn as much as possible about the subject in order to consider all possible angles that the project could lead. It is important to be knowledgeable about the topic you are designing for in order to accurately emulate what the client wants. Design includes the utilization of all media. Whether it is drawing, painting, or sculpting, I enjoy exploring different mediums in my art and bringing them to life on the computer. The computer offers a lot of opportunity to add effects and interest to a work of art, yet sometimes actually making a piece by hand illustrates a point even better. Exploration is key to broadening a designers ability, for this reason, I aim to expand my horizons as much as possible in order to develop my artistic skills across a large range of mediums. Simplicity is a key component of my designs. I often develop very complex ideas to begin, and then step-by-step I break down the ideas to be the most simplistic and direct as possible. Less is definitely more in the design world. It is my goal to be able to take the most complex ideas and turn them into straightforward, simple designs that do not distract from the main point that is being portrayed.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.